Pemberdayaan Petani Menyikapi New Normal Menggunakan Protokol Bekerja di Lahan dan Proses Distribusi Hasil Pertanian - Hairani Siregar; Ameilia Zuliyanti Siregar; Ritha F Dalimunthe; Syahfitri Nasution; Syarifah Syarifah (Universitas Mathla'ul Anwar Banten, 2021)
EMPOWERMENT OF FARMERS RESPONDING TO THE NEW NORMAL USING THE WORKING PROTOCOL IN THE LAND AND THE DISTRIBUTION PROCESS OF AGRICULTURAL PRODUCTS. Tanjung Morawa Village, located in Deli Serdang District, North Sumatra Province, has a development potential for agricultural land from food crops, horticulture and secondary crops and agro-ecotourism. The purpose of carrying out community service activities is to determine the potential of natural resources in the agricultural sector, especially “rice field tourism” as agro-ecotourism locations. Standard protocols and modules have not been made for farmers working on the land, at home, or during the distribution of agricultural products during the New Normal Period. For example, farmers rarely use masks, smoke, do not distance between farmers, or do not use gloves when spraying pests on the land. This service was held on 3 August 2020 which attended by 12 rice farmers in Tanjung Rejo Village, Tanjung Morawa, Deli Serdang Regency, North of Sumatera, with the socialization method for Standard Operational Procedure (SOP) Farmer Protocol in New Normal. This was followed by training on integrated pest control for rice plants using Yellow Sticky Traps, Sweep Net and vegetable pesticides. Therefore, it is necessary to formulate and socialize Protocols and Modules for Farmers to work on the land, interaction at home with family members and when buying and selling in the market, or distribution of agricultural products to support national of food security.